Enterprise 2.0 : new collaborative tools for your organization's toughest challenges - McAfee, Andrew. (Harvard Business Press, 2009)
"Most organizations realize that to succeed in today's turbulent world, they need to perform as an integrated whole to tap into innovations and good ideas. Yet many still find it difficult to capture the collective intelligence of their employees and customers. Companies don't know what they know--but they need to learn soon. Thanks to a new class of collaborative technologies, organizations can now leverage information in valuable new ways, including: capturing accumulated knowledge, connecting employees who need information with the experts who have it, and enabling the best ideas to emerge organically. These technologies--labeled "Web 2.0"--First appeared on the Internet, where they powered successful social communities and collaborative platforms like Facebook and Wikipedia. Web 2.0 tools, practices, and philosophies are now being deployed by a wide range of organizations, making them more agile, productive, and innovative. This is the phenomenon of Enterprise 2.0. In this compelling book, Andrew McAfee--a veteran researcher and writer on the business impact of technology, and the originator of the phrase "Enterprise 2.0"--describes the power of Enterprise 2.0 and shows readers how to harness it"--Cover, p. 2.